The Sage in Israel and the Ancient Near East. Edited by John G. Gammie and Leo G. Perdue. Pp. vii + 545. Winona Lake, IN: Eisenbrauns, 1990. isbn 0 931464 46 3 - Dell, Katharine (The journal of theological studies, 2005)
A Key contribution to the corpus of books on the wisdom literature, this book focuses on the sage in literary, historical, theological, and social context. It is wide-ranging in its scope in the way it treats sages from all parts of the ancient Near Eastern world—Egypt, Sumer, Mesopotamia, Ugarit, and ancient Iran. In fact, the grounding of the wisdom enterprise in the wider ancient Near Eastern world comes across strongly in this volume. There is a particular focus on the social locations and functions of sages in these different cultural worlds and on the sage as revealed by biblical and other texts.